2017
DOI: 10.14238/pi57.1.2017.18-22
|View full text |Cite
|
Sign up to set email alerts
|

Domperidone and maternal milk volume in mothers of premature newborns

Abstract: Background Mothers of premature newborns often have diffi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 10 publications
0
17
1
1
Order By: Relevance
“…The details are listed in Table S3. No maternal side effects were reported in four trials of domperidone 28,29,33,35 and one trial of metoclopramide 37 . Neonatal side effects were reported in three trials of domperidone 28,29,34 and two trials of metoclopramide 36,37 .…”
Section: Side Effectsmentioning
confidence: 95%
See 4 more Smart Citations
“…The details are listed in Table S3. No maternal side effects were reported in four trials of domperidone 28,29,33,35 and one trial of metoclopramide 37 . Neonatal side effects were reported in three trials of domperidone 28,29,34 and two trials of metoclopramide 36,37 .…”
Section: Side Effectsmentioning
confidence: 95%
“…Furthermore, literature retrieval was re-run before the final analysis (in February 2020) and no eligible trial was found. Therefore, fifteen studies were ultimately retained for qualitative synthesis [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] , and twelve trials were entered into the meta-analysis (see Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations